Crystallization behavior and mechanical properties of (Al90Fe5Ce5)100−xTixamorphous alloys - Singh D.; Singh D.; Mandal R.K.; Srivastava O.N.; Tiwari R.S. (My University, 2025)
The crystallization behavior and mechanical properties of melt-spun (Al90Fe5Ce5)100−xTix(x = 0, 4, 8 and 12 at.%) alloys have been investigated. The amorphous phase seems to be stable up to x = 8. The crystallization products for the amorphous alloys with x = 0–8 mainly composed of fcc-Al and icosahedral phases in the glassy matrix. The load dependent hardness behavior of amorphous alloys with and without Ti addition has been studied. The hardness value of the amorphous alloys has been found to be 3.72 and 3.07 GPa for x = 0 and 8 at 100 g load respectively. The annealed ribbons have higher hardness and strength as compared to that of as-synthesized ribbons. The enhanced values of hardness of the (Al90Fe5Ce5)100−xTix(x = 0, 4 and 8) alloys are attributed to the combined effects of icosahedral nanoparticles and Al nanoparticles in amorphous matrix. The absence of cracks around the indentation area up to 500 g of load for amorphous alloys suggests better capability to resist crack propagation in comparison to the annealed alloys. The formation of shear bands around the indentation periphery has been observed. The number of visible shear bands for the as-synthesized ribbons is higher in comparison to those of annealed ribbons. The values of yield strength and Meyer exponent of these alloys are also compared. © 2016 Elsevier B.V.